A new Andean species of Ablabesmyia Johannsen from Colombia (Diptera: Chironomidae) with an updated taxonomic key for Neotropical species. (3rd May 2020) - Dantas, Galileu P. S.; Amat, Eduardo; Hernández-Rangel, Sandra M.
ABSTRACT: Ablabesmyia: is a speciose genus, with about 90 species distributed worldwide, 37 of which occurring in the Neotropical region. In Colombia, A. metica is the only species of the genus recorded so far, which was initially described with material collected in the Colombian Orinoquia and more recently recorded in the southeastern Brazil. In the present study, Ablabesmyia opita sp. n. from the Colombian Andes is described and illustrated based on adult males collected at the inter-andean valley of Magdalena river basin. In addition, an updated taxonomic key for Neotropical species and a map of Ablabesmyia records in Colombia are provided. The male of the new species is similar to that of A. laurindoi but can be easily distinguished by the coloration patterns of the legs, the shape of the sternapodeme and by the number of antepronotals. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A9FD43D5-7018-4B3F-925B-E843B82D71E6